The role of adenotonsillectomy in the treatment of primary nocturnal enuresis in children: A systematic review. Issue 1 (February 2018) - Lehmann, Kyle Jeffrey; Nelson, Ralph; MacLellan, Dawn; Anderson, Peter; Romao, Rodrigo L.P.
Summary: Introduction: Primary nocturnal enuresis (PNE) is a challenging condition for physicians, patients and families. Although the etiology remains unclear, sleep-disordered breathing (SDB) and sleep apnea have been suggested to play an important role. Recent research has suggested a potential therapeutic benefit of adenotonsillectomy (T&A) and surgical management of upper airway obstruction in the treatment of PNE. Objective: The aim was to conduct a systematic review of relevant literature to determine the effectiveness of T&A in treating children aged 2–19 years with PNE. Study design: This was a systematic review using a comprehensive electronic search strategy that included PubMed, Embase, CINAHL, Cochrane Library, conference proceedings, and the gray literature up to July 2015. We included all studies of children aged 2–19 years with PNE and SDB who underwent T&A. The primary outcome was resolution of PNE following surgery. Observational studies and randomized trials were reviewed. Risk of bias assessment and meta-analyses of included studies were performed. Results: We screened 3254 citations; following title and abstract screening, 42 studies were selected for full-text screening by two independent reviewers. We included 18 studies (890 patients) in our final analysis. All studies were observational and only one included a control group. Meta-analysis of proportions of all (18) studies revealed a pooled complete resolution rate of 51% (43–60%), with significant heterogeneity among studies ( I 2 = 82.2%). Partial resolution was seen in 20% (14–27%), with similar heterogeneity to the complete resolution group. Sensitivity analysis including only studies with a low risk of bias and with patients ≥5 years ( n = 244 patients) yielded a complete resolution rate of 43% (36–49%) with minimal heterogeneity ( I 2 = 0%; figure). Conclusion: In our systematic review, T&A resulted in improvement of nocturnal enuresis in more than 60% of patients, with complete resolution rates in excess of 50%. Findings were persistent on meta-analysis focused only on studies including older patients (≥5 years) and those with short follow-up after surgery (≤3 months), which imply a higher cure rate than would be expected based on natural history alone. The limitations of this review include the lack of controlled trials, the overall quality of the evidence reviewed and the heterogeneity between included studies. The role for systematic investigation and treatment of sleep disorders in patients with PNE should be scrutinized further, since a near 50% complete resolution rate for PNE may be expected with T&A in some settings. Figure Meta-analysis of proportions of complete resolution of primary nocturnal enuresis. Studies with a low risk of bias and in children ≥5 years of age.